Nephrocurative Effect of Parthenium hysterophorus (Carrot Grass) in Paracetamol Induced Nephrotoxicity in Rabbits: Nephrocurative Effect of Parthenium hysterophorus - Makhdoom, Sheeba; Maqbool, Ayesha; Muhammad, Hafsah; Makhdoom, Munazza; Ashraf, Hamna; Khan, Waseem Ahmed; Irfan, Muhammad (Cellular and Molecular Biology, 2022)
Parthenium hysterophorus is conventionally used to treat urinary tract infections, joint pain, and hyperglycaemia. This study evaluates the reno-curative effects of methanolic extract of P. hysterophorus (MEPH) in paracetamol-induced nephrotoxic rabbits. Thirty male rabbits were divided into V groups: Group I served as the negative control. Group-II to V were treated with 2 g/kg of paracetamol to induce nephrotoxicity. Group II served as paracetamol (PCM) intoxicated control. Group III till V were fed orally with the following treatments: III paracetamol (PCM) 40 mg/kg MEPH; IV PCM+80 mg/kg MEPH; V PCM+Cystone (5 ml/kg), respectively, for 14 days. The body weight of all animals was recorded on days 1, 7 and 14. All the animals were dissected on the 14th day and blood, urine and kidneys were collected. The results showed that P. hysterophorus had no effect on body weight but lowered urea and creatinine levels and brought urine parameters back to the normal range in experimental groups of PCM-induced nephrotoxic rabbits. The 80 mg/kg dose of MEPH reduced urea and creatinine levels and normalized urine parameters more effectively compared to low doses of MEPH and the standard drug, i.e., Cystone. Kidney histopathological studies exhibited that 80 mg/kg of MEPH repaired paracetamol-induced renal damage, whereas Cystone only provided reno protection as no repair in damaged tissue was investigated in histopathology of Cystone treated animals. The results suggested that P. hysterophorus exhibited significant reno-curative activity on paracetamol-induced nephrotoxic rabbits.